SELEKSI CALON INDUK BERDASARKAN NILAI PEMULIAAN BOBOT SAPIH KAMBING PERANAKAN ETAWAH DI KECAMATAN METRO SELATAN, KOTA METRO - Fikri Syahputra; Idalina Harris; Sulastri . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
Breeding Value (BV) is an evaluation of the quality of animal genetics for a certain characterwhich is given relatively based on it‘s position in population. This study aimed to determine theheritability and repitability value of weaning weight of Etawah Crossbred Goat, to determine theweaning weight and BV of each individual female goat, and to determine the individual femaleswhich had the highest BV of weaning weight. This study used the survey method to obtain thesubject matter, which comprised 40 female parents which had recording of age when littering,pedigree of male, and goatling of female parent samples which had recording of birth weight, typeof birth, type of maintenance, and weaning weight of the first and second birth.The result of this study showed that : the average of weaning weight corrected was 20,980±1,080kg; the heritability value of weaning weight was 0,135±0,010; the repitability value of weaningweight was 0,389; the average of BV of weaning weight was 20,981±0,214. Based on the result ofthis study, it was known that 24 (60%) of 40 Etawah Crossbred Goat female parents had higherBV over the average, and 5 female parents were given priority with the highest BV of weaningweight, those were the goat female parents with code C1 with BV of 21,369; H1 of 21,229; F2 of21,267; G3 of 21,261; E2 of 21,230.